Multi-harmonic homodyne approach for optical property measurement of turbid medium in transmission geometry - Ho, Jun Hui (2013)
The accurate determination of both absorption and scattering properties in homogeneous diffuse medium is critical in many applications of diffuse optical imaging, especially in clinical applications such as breast cancer diagnosis. In this paper, we report a frequency-domain method to simultaneously measure both absorption and reduced scattering coefficients (μa and μs′) in transmission geometry, based on a parallel homodyne approach using a RF-modulated laser source and a gain-modulated image intensifier. This method enables fast multi-pixel phase-sensitive measurement, which leads to an efficient way to obtain μa and μs′ values via the well-known analytical Green's function solution in slab geometry. We developed an approximate formula of the analytical solution that is especially suitable for multi-pixel data analysis. In addition, we present a comprehensive multi-harmonic data analysis that includes DC data, which offers multi-frequency information from a single-frequency dataset, hence leading to improved accuracy and stability in measurement.